2020
DOI: 10.1101/2020.09.08.287482
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antibody binding to SARS-CoV-2 S glycoprotein correlates with, but does not predict neutralization

Abstract: Convalescent plasma from SARS-CoV-2 infected individuals and monoclonal antibodies were shown to potently neutralize viral and pseudoviral particles carrying the S glycoprotein. However, a non-negligent proportion of plasma samples from infected individuals as well as S-specific monoclonal antibodies were reported to be non-neutralizing despite efficient interaction with the S glycoprotein in different biochemical assays using soluble recombinant forms of S or when expressed at the cell surface. How neutraliza… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 28 publications
1
26
0
Order By: Relevance
“…Therefore, the sVNT assay, although not yet approved for diagnostic application, is superior for a clinical setting and allows the fast screening of convalescent plasma samples in low biosafety level laboratories. Also other ELISA-based sVNT assay systems have been developed recently ( Bošnjak et al, 2020 ), ( Abe et al, 2020 ), ( Ding et al, 2020 ) and different kits are commercially available. Assay comparisons were performed by multiple groups and overall, the sVNT assays correlated well with the other neutralization assays ( Abe et al, 2020 ), ( Meyer et al, 2020 ), ( Bond et al, 2020 ), ( McGregor et al, 2020 ), ( Bošnjak et al, 2020 ), ( Ding et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the sVNT assay, although not yet approved for diagnostic application, is superior for a clinical setting and allows the fast screening of convalescent plasma samples in low biosafety level laboratories. Also other ELISA-based sVNT assay systems have been developed recently ( Bošnjak et al, 2020 ), ( Abe et al, 2020 ), ( Ding et al, 2020 ) and different kits are commercially available. Assay comparisons were performed by multiple groups and overall, the sVNT assays correlated well with the other neutralization assays ( Abe et al, 2020 ), ( Meyer et al, 2020 ), ( Bond et al, 2020 ), ( McGregor et al, 2020 ), ( Bošnjak et al, 2020 ), ( Ding et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Using a recombinant SARS-CoV-2 S ectodomain (S2P) as a bait to identify antigenspecific B cells, we collected and screened a library of S-targeted BCR clones and identified two most potent NAb candidates: CV3-1 and CV3-25. We first characterized their epitope specificity using ELISA, cell-surface staining, virus capture assay and surface plasmon resonance (SPR) (Ding et al, 2020;Prevost et al, 2020). Both NAbs recognized SARS-CoV-2 S efficiently with a low-nanomolar affinity, as a stabilized ectodomain (S-6P) or when displayed on cells and virions (Figure 3A-E).…”
Section: Highly Potent Sars-cov-2 Nabs Cv3-1 and Cv3-25 From A Convalescent Donormentioning
confidence: 99%
“…The SARS-CoV-2 virus capture assay was previously reported (Ding et al, 2020). Briefly, pseudoviral particles were produced by transfecting 2×10 6 HEK293T cells with pNL4.3 Luc R-E- and 50 μL of 1 mM D-luciferin potassium salt (ThermoFisher Scientific).…”
Section: Virus Capture Assaymentioning
confidence: 99%
“…Indeed, several studies have demonstrated SARS-CoV-2 S cross-reactivities involving closely related coronaviruses (9)(10)(11)(12) along with others such as dengue virus (13,14) and HIV(15). Investigation of such crossreactive interactions may reveal novel viral epitopes and vulnerabilities, along with providing context for the interpretation of serological assay studies, of which some have failed to demonstrate antibody titers as an appreciable predictor of immunity, disease status, and disease progression for COVID-19 (16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Using pseudo-typed viral entry assays, we demonstrate these cross-reactivities to be non-neutralizing, and likely incapable of mediating ADE via FcγRII receptor engagement.In response to the global COVID-19 pandemic, a plethora of SARS-CoV-2 serological testing strategies have emerged(4)(5)(6)(7)(8), with the goal of providing epidemiological, diagnostic, and prognostic insight to health care providers. Such strategies have primarily focused on the detection of antibodies which bind the SARS-CoV-2 spike or nucleocapsid (N) proteins, however, recent studies have failed to demonstrate an appreciable predictive value between antibody titers and viral neutralization, disease status, and disease progression(16)(17)(18)(19). While concurrent assessment of aspects of cellular immunity will likely contribute predictive value in such studies, efforts to further characterize humoral responses beyond serological detection of antigen-binding antibodies can provide a critical context for the interpretation of results.Assessments of aggregate antibody titers are incapable of differentiating between low affinity, non-neutralizing and high affinity, neutralizing antibodies, limiting their clinical utility.…”
mentioning
confidence: 99%